Farmers' experiments in Cuba. Issue 1 (5th December 2012) - Leitgeb, Friedrich; Kummer, Susanne; Funes-Monzote, Fernando R.; Vogl, Christian R.
Abstract: Due to the collapse of the socialist systems in 1989, Cuba's government promoted a series of structural changes to deal with resource scarcity and to enhance agricultural productivity. The upcoming crisis triggered adaptation strategies and led to a large-scale transition process towards a more sustainable model of agriculture. Farmers' experiments have been an implicit part of this process. Nowadays, farmers' capacity to experiment is widely accepted among the scientific community. However, detailed descriptions of farmers' approaches to experimentation are scarce. In this study, we examine the topics, resources, sources, motives, methods and outcomes of farmers' experiments in Cuba. The research methods comprised semi-structured interviews with 72 Cuban farmers, field notes, participant observation and a research diary. Key informants and 34 expert interviews added important insights into analysis. The results reveal that farmers' experiments are an integral part of farming in Cuba. Most farmers reported realizing their own experiments on their farms. The use of locally available resources was a crucial element for farmers' experiments. The topics were related to the introduction of new plant species or varieties, plant production, mechanization, fertilization, plant protection and the introduction of new animal species. The farmers' own idea was the most important source for experimenting, followed by ideas offered by colleagues and family members. Increasing production, independence from external resources and improving farm management were the main motives for experimenting. More than half of the farmers started to experiment without detailed written or mental planning, but made some considerations about the experiment before starting. Some planned more in detail and a few farmers devised a written plan, draft or model. Starting on a small scale was a way to minimize risks. The experiments were mainly evaluated by observation and comparison. Only a few farmers took records of their experiments. The most important outcomes were higher production, food self-sufficiency, work easement, improved plant health, increased knowledge, higher working efficiency and better taste of products. Farmers' experiments are a means of learning and they enhance farmers' capacity to adapt to changing conditions.